Rancang Bangun Media Pembelajaran Interaktif Berbasis Game Edukasi Materi Rukun Sholat Dengan Menggunakan Metode Waterfall - Azwardi; Saputri, Rezi Winda; Rian Rahmanda Putra (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
This study aims to design and build game-based interactive learning media in PAI subjects with pillars of prayer material. This game was created as a learning medium for elementary school students at SD Negeri 07 Pedamaran. This educational game-based learning media application can be used as an alternative to learning media aids for students. The method used in designing and building applications using the waterfall method, consists of five stages, namely needs analysis, design, implementation, testing, and maintenance. Based on the results of application implementation and testing, that the application can run properly according to the required specifications, and can be used as a student learning medium. Quiz features contained in learning applications can be used as material for evaluating student learning